Protocol development for synchrotron contrast-enhanced CT of human hip cartilage. (November 2019) - Zhang, Honglin; Belev, George; Stewart, Rachel C.; Grinstaff, Mark W.; Snyder, Brian D.; Wilson, David R.
Highlights: A synchrotron contrast enhanced computed tomography (sCECT) protocol is described for imaging hip cartilage in unloaded and loaded cadaver specimens. Diffusion time and contrast agent distribution was assessed for 3 injection methods. Acetabular and femoral cartilage thickness was assessed with a 0.1 mm voxel size in unloaded conditions. Abstract: Understanding hip osteoarthritis requires new investigational tools for quantitative studies of biophysical and biomechanical properties as well as for determination of structure. Three new protocols to study pathological changes in cartilage and to measure cartilage thickness in intact human hips are described using synchrotron contrast enhanced computed tomography (sCECT) with the iodinated contrast agent CA4+. Ten human cadaver hips were prepared and injected with CA4+ using three different methods, all of which included rotation and distraction of the joint. CA4+ diffusion into cartilage was monitored using sCECT. The thickness of acetabular and femoral cartilage was also measured. Diffusion times ranged from 2 h to 75 h, depending on the injection protocol and the cartilage region. Direct single injection of the contrast through the labrum resulted in the fastest diffusion times. The iodine attenuation coefficient, which reflects the contrast agent distribution in the cartilage, ranged from 0.0142/cm to 0.1457/cm. Three injections at the head/neck conjunction area yielded the highest iodine attenuation coefficients in cartilage. The femoral cartilage in the Superior-Medial compartment was significantly thicker than in the other 3 femoral compartments, and femoral cartilage in the Superior-Anterior compartment was significantly thinner than the other 3 femoral compartments. The acetabular cartilage in the Superior compartment was significantly thicker than that in the Superior-Posterior compartment. sCECT with CA4+ allows assessment of hip cartilage thickness with 0.1 mm isotropic voxel size, sufficient for evaluating cartilage pathology and biomechanics.